2004
DOI: 10.1016/j.crme.2004.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Self-excited stick–slip oscillations of drill bits

Abstract: This Note studies the self-excited stick-slip oscillations of a rotary drilling system with a drag bit, using a discrete model which takes into consideration the axial and torsional vibration modes of the bit. Coupling between these two vibration modes takes place through a bit-rock interaction law which accounts for both frictional contact and cutting processes at the bit-rock interface. The cutting process introduces a delay in the equations of motion which is ultimately responsible for the existence of self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(82 citation statements)
references
References 7 publications
2
80
0
Order By: Relevance
“…With those conclusions in mind, a control strategy is suggested in (Jansen and Van den Steen, 1995) that torsional vibrations the in drill-string systems should be avoided. It should be noted that Germay (Germay, 2002) and Richard et al (Richard et al, 2004) concluded that the interaction between torsional and axial dynamics of the system may cause torsional vibrations in the drilling systems. Such interaction effectively leads to the Stribeck effect, according to these authors.…”
Section: Real Drilling Systemsmentioning
confidence: 99%
“…With those conclusions in mind, a control strategy is suggested in (Jansen and Van den Steen, 1995) that torsional vibrations the in drill-string systems should be avoided. It should be noted that Germay (Germay, 2002) and Richard et al (Richard et al, 2004) concluded that the interaction between torsional and axial dynamics of the system may cause torsional vibrations in the drilling systems. Such interaction effectively leads to the Stribeck effect, according to these authors.…”
Section: Real Drilling Systemsmentioning
confidence: 99%
“…The exponential decaying behaviour coincides with experimental torque values and is inspired in the models given in [1], [3], [21], [24].…”
Section: A Model Describing Drillstring Torsional Behaviourmentioning
confidence: 99%
“…This model is proposed in [24] for PDC bits and considers the coupling between axial and torsional vibrations. The axial drilltring dynamics is considered through the introduction of the vertical varying force W ob affecting the bit.…”
Section: An Alternative Model For the Torque On The Bitmentioning
confidence: 99%
See 2 more Smart Citations